Cleft Care UK study. Part 5: child psychosocial outcomes and satisfaction with cleft services. (November 2015) - Waylen, A.; Ness, A. R.; Wills, A. K.; Persson, M.; Rumsey, N.; Sandy, J. R.
Structured Abstract: Objectives: To describe the impact of cleft service centralization on parental perceptions of child outcomes and satisfaction with care from the Cleft Care UK (CCUK) study and compare them to the Clinical Standards Advisory Group (CSAG) study that took place 15 years earlier. Setting and Sample Population: A subgroup of respondents from a UK multicentre cross‐sectional study (CCUK) of 5‐year‐olds born with non‐syndromic unilateral cleft lip and palate. Materials and Methods: Data on parents' perceptions of child self‐confidence and their satisfaction with treatment outcomes and service provision were collected via self‐report questionnaires. Data were compared with findings from the 1998 CSAG study. Results: Fewer parents in the CCUK study perceived their children as having poor self‐confidence than in the 1998 CSAG study (8 and 19%, respectively). At least 81% of parents report satisfaction with the child's facial features after surgery and 98% report being satisfied with the care received. These results are similar to those reported in 1998. There is no evidence of an adverse impact on families' ability to attend appointments at the cleft clinic following centralization. Levels of reported problems (around 30%) with attendance were similar to those reported by CSAG. Conclusion: Centralization of cleft services appears to have improved parental perceptions of some child outcomes but has made little difference to already high levels of parental satisfaction with cleft care services. Centralization is not associated with an increase in the proportion of families who find it difficult to attend appointments.